Funcionalização da palha de milho com 3-aminopropiltrietoxisilano para adsorção do corante vermelho reativo 141 - Carijo, Paola Mortari (2019)
An alternative and low cost adsorbent (CS–APTES) was developed by the functionalization corn stover (CS) with 3–aminopropyltrietoxysilane (APTES) using a simple method of reaction under reflux. The techniques of Fourier transformed infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), point of zero charge (pHpzc) and N2 isotherm (BET) were used characterize the developed material and investigate the functionalization, and CS–APTES was employed to adsorb Reactive Red 141 (RR141) dye from aqueous solutions. The functionalization with APTES led to an increase of 15 times in the adsorption capacity. The adsorption of RR141 on CS–APTES was favored at pH of 3.0 and using a dosage of 3.0 g L–1. The adsorption equilibrium was reached within 4h, being the process thermodynamically favorable, endothermic and controlled by chemisorption, with an enthalpy variation (ΔH0) of 110,17 kJ mol-1. The maximum adsorption capacity was 15.65 mg g–1. The adsorption process was better described by the Langmuir isotherm model, and the pseudo second order kinetic model. CS–APTES was efficient to treat a colored effluent containing other ions and molecules. The use of 10 g L–1 of CS–APTES was sufficient to decolorize more than 98% of this effluent. The CS–APTES material can be easily prepared from CS, generating an efficient and low cost adsorbent, which in turn, is able to treat colored effluents.